Percutaneous thermal ablation combined with transcatheter arterial chemoembolization for hepatitis C virus-related hepatocellular carcinoma: Efficacy and survival - Sun, Yu; Zhang, Honghai; Long, Jiang; Zhang, Yonghong; Zheng, Jiasheng; Yuan, Chunwang (Frontiers in Oncology, 2022)
Objective: The aim of this study was to investigate the efficacy and survival of Hepatitis C virus (HCV) -related hepatocellular carcinoma (HCC) undergoing percutaneous thermal ablation combined with transcatheter arterial chemoembolization (TACE). Methods: A total of 83 HCV-related HCC patients who were treated with percutaneous thermal ablation combined with TACE were retrospectively analyzed. The demographic and clinical data were collected. The overall survival(OS) and recurrence free survival(RFS) rates were assessed by the Kaplan-Meier method. Univariate and multivariate Cox regression analysis was used to assess independent risk factors of OS and RFS. Results:92.8% patients (77/83) and 96.6% (170/176) tumor lesions achieved complete response (CR)1 month after all treatment, and 10.8%(9/83) patients had minor complications. The median OS was 60 months (95% confidence interval(CI)= 48.0-72.0), and the 1-, 2-, 3-, 5- and 10-year cumulative OS rates were 94%, 78.3%, 72.3%, 43.4% and 27.5%, respectively. The cumulative RFS rates at 1-, 2-, 3- and 5-year were 74.7%, 49.3%, 30.7% and 25.3%, respectively. Sex(HR =0.529, P=0.048), ablation result(HR=5.824, P=0.000) and Albumin-bilirubin(ALBI) score (HR=2.725, P=0.011)were independent prognostic factors for OS. Alpha-fetoprotein (AFP) (HR =2.360, P = 0.005) and tumor number(HR=2.786, P=0.000) were independent prognostic factors for RFS. Conclusions: Percutaneous thermal ablation combined with TACE is a safe and effective treatment for HCV-related HCC. Sex, ablation result and ALBI are significant prognostic factors for OS. AFP and tumor number are significant prognostic factors for RFS.